Unravelling the challenges of rehabilitation and treatment of musculoskeletal disorders in professional ballet dancers - Benoit Piau, J.; Bolling, C.; Morin, M.; Verhagen, E. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Dancers are among the most injured athletes, which will cause repercussions on their physical and mental health, as well as their career (1,2). It is essential to establish strategies to prevent and manage these injuries. However, some challenges arise when preventing and treating injuries, as reported by dancers and health professionals (3). This study explored the experiences and challenges faced by the dancers and staff in a ballet company regarding the rehabilitation and treatment of injuries.